Economic Losses due to Important Diseases of Dairy Bovines in Sabarkantha District of Gujarat - Dadawala, Abidali I; Makwan, Paresh P; Bhati, Naresh B; Kapadiya, Falgun M; Patel, Komal N; Deshpande, Satish B (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Surveillance on production loss due to major diseases in cattle and buffaloes of Sabarkantha District was carried out with total 184 livestock owners from 07 Talukas to work out their economic impact. A questionnaire was constructed to record the information of various disease occurrences, production losses and treatment cost of animals, including socio-economic and other characteristics of farmers. The morbidity rates of different diseases were determined. The findings revealed that the maximum respondents (85.32 %) had different level of school or college education and only 14.68 % respondents were illiterate in the district. The majority of the farmers covered their animals under vaccination regularly against Foot-and-Mouth disease (FMD) and Haemorrhagic Septicaemia (HS) and only a few adopted for Theileriosis. Majority of respondents (71.20%) adopted deworming their animals for the prevention of different parasitic problems. Majority of infectious and metabolic diseases including infertility and mastitis caused drop in milk production, and Brucellosis was at the top in total loss per animal. Morbidity of various diseases was more in buffaloes than in cows (25.21 vs. 14.43%) and thereby the economic losses also. The highest total economical loss per animal from treatment and decline milk production was from Brucellosis (Rs. 1806.54) followed by Mastitis (Rs. 1193.60), FMD (Rs. 982.66), Uterine infections (Rs. 754.72), Babesiosis (Rs. 739.17), Milk fever & Ketosis (Rs. 597.50 & 550.67), Infertility (Rs. 542.83) and others. These findings suggest the need for sustained active surveillance program, and development and use of novel diagnostics for early detection of the diseases so as preempt their adverse impact on livestock economics.